Perkembangan Kognitif Anak Usia Dini Melalui Kegiatan Bermain Pengklasifikasian Benda Alam - Sari, Dilla Puspita; Syofiyanti, Dessy (PeDaPAUD: Jurnal Pendidikan Dasar dan PAUD, 2025)
Cognitive development is an important aspect in early childhood growth, because it directly affects the ability to think, understand, and solve problems. However, many early childhood children experience obstacles in their cognitive development. One effective way to stimulate this aspect is through meaningful play activities, especially by using media from natural materials. This study aims to improve the cognitive development of early childhood through natural object classification play activities. This study uses the Library Research method. The primary sources used are research results related to the topic of discussion in this study and several secondary sources, such as printed and digital books. Data analysis uses the Content analysis method. The results of the study show that classification play activities using natural media can improve children's cognitive abilities, especially in terms of grouping objects based on color, shape, and size. Children become more active, interested, and motivated during the learning process. Thus, natural media has proven to be effective as a concrete and fun learning aid in improving the cognitive development of early childhood.